1993
DOI: 10.1042/bj2890533
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutation studies of human liver cytochrome P-450 isoenzymes in the CYP2C subfamily

Abstract: Evidence from human studies in vivo and in vitro strongly suggests that the methylhydroxylation of tolbutamide and the 4-hydroxylation of phenytoin, the major pathways in the elimination of these two drugs, are catalysed by the same cytochrome P-450 isoenzyme(s). In the present study we used site-directed mutagenesis and cDNA expression in COS cells to characterize in detail the kinetics of tolbutamide and phenytoin hydroxylations by seven CYP2C proteins (2C8, 2C9 and variants, and 2C10) in order to define the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 26 publications
6
72
0
Order By: Relevance
“…Additionally, CYP2C8 is involved, to a minor extent, in the metabolism of the sulfonylureas gliclazide, glyburide, and tolbutamide, the dipeptidyl peptidase 4 inhibitor sitagliptin, and the PPARa agonist sipoglitazar (Table 1; Relling et al, 1990;Srivastava et al, 1991;Veronese et al, 1993;Elliot et al, 2007;Vincent et al, 2007;Zharikova et al, 2009;Nishihara et al, 2012). Tolbutamide p-methyl hydroxylation has been used as a marker reaction for CYP2C8 activity in several in vitro studies.…”
Section: A Drugsmentioning
confidence: 99%
“…Additionally, CYP2C8 is involved, to a minor extent, in the metabolism of the sulfonylureas gliclazide, glyburide, and tolbutamide, the dipeptidyl peptidase 4 inhibitor sitagliptin, and the PPARa agonist sipoglitazar (Table 1; Relling et al, 1990;Srivastava et al, 1991;Veronese et al, 1993;Elliot et al, 2007;Vincent et al, 2007;Zharikova et al, 2009;Nishihara et al, 2012). Tolbutamide p-methyl hydroxylation has been used as a marker reaction for CYP2C8 activity in several in vitro studies.…”
Section: A Drugsmentioning
confidence: 99%
“…A fruitful alternative consists of the expression of cloned cDNA, coding for individual forms of P450 enzymes, in an adequate heterologous system. Several human liver P450 from the subfamilies involved in xenobiotic oxidation have already been expressed in different systems, including recombinant simian virus 40 in COS cells and references therein; Romkes et al, 1991;Veronese et al, 1991), recombinant vaccinia viruses in human hepatoma Hep G2 cells (Aoyama et al, 1990a and1990b, and references therein) and recombinant plasmids in the yeast Succharomyces cerevisiae (Yasumori et al, 1989;Brian et al, 1989;Brian et al, 1990;Renaud et al, 1990;Eugster et al, 1990;Ching et al, 1991; Truan, G., Cullin, C., Reisdorf, P., Urban, P. and Pompon, D., unpublished results). P450 NF25 (CYP3A4) is important in pharmacology and toxicology, not only because it is probably the major form of human liver (Guengerich and Turvy, 1991) but also because it is involved in the metabolism of numerous widely used drugs such as nifedipine (Guengerich et al, 1986a), erythromycin and troleandomycin (Renaud et al, 1990 and references therein), quinidine (Guengerich et al, 1986b), cyclosporin A (Kronbach et al, 1988;Aoyama et al, 1989;Combalbert et al, 1989), 1 7a-ethynylestradiol (Guengerich, 1988), midazolam (Kronbach et al, 1989), lidocaine (Bargetzi et al, 1989;Imaoka et al, 1990), and diltiazem (Pichard et al, 1990).…”
mentioning
confidence: 99%
“…Before the present study, the only information available regarding specific CYP2C9 amino acids that may influence the interaction between the enzyme and phenytoin came from in vitro studies that evaluated the effect of CYP2C9 genetic variants on phenytoin turnover (Veronese et al, 1993;Rettie et al, 1999;Takanashi et al, 2000). These early studies demonstrated that expression of the CYP2C9*2 (R144C) and CYP2C9*3 (I359L) alleles resulted in diminished metabolism of phenytoin because of a reduction in K m , K cat , or a combination of these two kinetic effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, beyond a single report that the I359L (CYP2C9.3) variant increases the percentage of (R)-p-HPPH produced (Takanashi et al, 2000), nothing is known about phenytoin's binding determinants within the active site of CYP2C9. This is especially surprising because one of the first studies employing sitedirected mutagenesis to investigate the activity of CYP2C9 genetic variants involved phenytoin as the probe drug (Veronese et al, 1993).…”
mentioning
confidence: 96%
See 1 more Smart Citation